Optimizing and strengthening the productivity of lecturer’s scientific work - Lina Novita; Elly Sukmanasa; Eka Suhardi; Suhendra Suhendra (Institute of Advanced Engineering and Science, 2023)
The productivity of lecturers’ scientific work is an important factor in career advancement, quality of study programs, and university rankings. The research aimed to strengthen and optimize the productivity of lecturers’ scientific work. The research method used is modeling and steering optimization (POP-SDM), data analysis using path analysis by looking for mathematical model equations. Scientific Identification Theory of Operation Research in Education Management (SITOREM) analysis is carried out to improve weak indicators and maintain strong indicators. The research was conducted on lecturers at private universities as many as 197 respondents. The qualitative research findings indicate that creativity, academic culture, knowledge management, and professional commitment were mentioned in the interviews. The results of quantitative research prove that creativity, academic culture, knowledge management, and professional commitment affect the productivity of lecturers’ scientific work. Research finds novelty through the SITOREM approach, by conducting an analysis to identify indicators of the variables studied in order to determine indicators that are good enough to be maintained and indicators that are still weak and need to be improved. The SITOREM approach can be in the form of a model for developing scientific papers for lecturers as a model of behavior, constellation patterns, and guidelines for the productivity of scientific works produced by lecturers.